Formulation and Testing of Antioxidant Activity of Papaya Fruit (Carica papaya L.) Extract Spray Gel Using the DPPH Method - Hapsari, Fauziyyah Kunti; Hidayati, Nurul (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2025)
Methanol extract of papaya fruit possesses natural antioxidant activity that can be utilized to counteract free radicals. Spray gel is a formulation with low viscosity that can remain in contact for an extended period when sprayed on the skin. This study aims to formulate a spray gel made from papaya fruit extract and evaluate its antioxidant activity using the DPPH method. The papaya fruit extract was prepared using the maceration method with methanol as the solvent. Three spray gel formulas with papaya fruit extract concentrations of 1%, 2%, and 3% were tested for their physical properties. The testing revealed that Formula III (with a 3% extract concentration) met the appropriate pH criteria (5.67 ± 0.058), the desired viscosity (41.1 ± 2.84 cps), and the fastest drying time (< 5 minutes). The antioxidant activity test yielded the lowest IC50 value for Formula III at 330.307 ppm, followed by Formula II (IC50 = 374.08 ppm) and Formula I (IC50 = 455.21 ppm). All three formulas exhibited good sprayability and spreadability, but their antioxidant activity was relatively weak. Formula III with a 3% extract concentration is considered the best option based on physical criteria and antioxidant activity, contributing to developing a product that can protect the skin from UV damage.